Conceptualizing music cognitive structure, theory, and analysis - Zbikowski, Lawrence Michael; Oxford eBooks (Oxford : Oxford University Press, 2002)
This text shows how work in cognitive science, especially that developed by cognitive linguists and cognitive psychologists can be used to explain how we understand music. The book focuses on three cognitive processes - categorization, cross-domain mapping, and the use of the conceptual model.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Musical perception; Musical analysis; Cognition; Electronic books